Kegiatan Menulis dan Membaca Huruf Hijaiyah dengan Menggunakan Metode Flashcard untuk Meningkatkan Kemampuan Anak Usia Dini di TPQ As-Sabiqun - Yuliastutik Yuliastutik; Zakiya Qothrun Nada; Nadhira Shava Putri Ramadhan (Lembaga Pengembangan Kinerja Dosen, 2025)
The ability to write and read hijaiyah letters is very important for students to understand Islamic teachings. The PKM team at TPQ As-Sabiqun uses the flash card method in learning hijaiyah letters to improve students' abilities. This method invites students to learn visually and interactively, and encourages them to be more active, confident, and enthusiastic. This literature study aims to analyze the activity of reading and writing hijaiyah letters using the flashcard method to improve the abilities of students at TPQ As-Sabiqun. This study uses the PAR (Planning, Acting, Reflecting) method. The results of this activity show a significant increase in students' abilities in learning to write and read hijaiyah letters using the flashcard method..